2012
DOI: 10.1007/s13577-012-0049-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transforming growth factor-beta1 on cell motility, collagen gel contraction, myofibroblastic differentiation, and extracellular matrix expression of human adipose-derived stem cell

Abstract: Human adipose-derived stem cells (ASCs) are adult pluripotent stem cells, and their usefulness in plastic surgery has garnered attention in recent years. Although, there have been expectations that ASCs might function in wound repair and regeneration, no studies to date have examined the role of ASCs in the mechanism that promotes wound-healing. Transforming growth factor-beta1 (TGF-β1) is a strong candidate cytokine for the triggering of mesenchymal stem cell migration, construction of extracellular matrices,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…We observed that these cells have contraction ability, corroborating data described by other laboratories [24,28,29,51]. Indeed, this is consistent with the gene expression profile of some contractile proteins studied in this work (Figures 3, 4A-C), and justifies the basal contraction potential similar to that of SMCs (32.3 ± 13% vs. 29.9 ± 10.9%, at 48 hours, n = 4).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We observed that these cells have contraction ability, corroborating data described by other laboratories [24,28,29,51]. Indeed, this is consistent with the gene expression profile of some contractile proteins studied in this work (Figures 3, 4A-C), and justifies the basal contraction potential similar to that of SMCs (32.3 ± 13% vs. 29.9 ± 10.9%, at 48 hours, n = 4).…”
Section: Resultssupporting
confidence: 93%
“…Mechanical stretch for 96 hours resulted in no change in this phenotype (28.1 ± 12.2%) (Figure 7B). On the other hand, it has been reported that hASCs chemical treatment, such as SPC or TGFβ, promotes increments in cell contraction [28,51]. Kim et al demonstrated that U46619 (Thromboxane A2 mimetic) treatment for 96 hours induces hASCs expression of some contractile proteins, which was associated with an almost 60% increase in contractility of these cells [29].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to bone marrow, adipose tissue constitutes an easily accessible source for large numbers of patient-derived MSCs, which have an enormous potential for future applications in tissue regeneration (Zuk, 2010). Importantly, hASCs have been shown to differentiate into myofibroblasts and CAFs under the influence of tumor-secreted factors, such as TGF-b, and to promote the in vitro invasiveness of breast cancer cells (Jeon et al, 2010;Jotzu et al, 2011;Kakudo et al, 2012). We found that MKL1_S, but not MKL1_L, was strongly upregulated in primary hASCs within 24 h of TGF-b-induced myofibroblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to study MKL1 isoform expression during myofibroblast differentiation, we used primary hASCs, which can be induced to differentiate into myofibroblasts by the addition of TGF-b1 (Kakudo et al, 2012). We isolated the stromal vascular fraction (SVF) of cells from patient adipose tissue, which was confirmed to contain a large proportion of mesenchymal stems cells (MSCs) expressing the mesenchymal markers CD73, CD90 and CD105 (Fig.…”
Section: Human Cells Express a Second Shorter Mkl1 Isoformmentioning
confidence: 99%
“…Myofibroblasts are central to wound healing and αSMA expressed by these myofibroblasts can increase cell adhesion necessary for cell spreading and migration of cells, thus playing an important role in the wound healing response. [29][30][31] According to Zhou et al, 17 reduced expression of αSMA and disturbed stress fiber arrangement is responsible for reduced migration of cells. In our study, during wound healing, TSA treatment prevented migration of cells and this Eye could be because of the reduction in expression levels of αSMA and disruption of stress fibers on TSA treatment.…”
Section: Discussionmentioning
confidence: 99%